OVERVIEW OF OPTIMIZING PATIENT SAFETY THROUGH THE IMPLEMENTATION OF DRUG CENTRALIZATION AT IBNU SINA GRESIK HOSPITAL - Gustomi, Mono Pratiko; Zahroh, Roihatul; Arizta NC, Lilyana (PT Altin Riset Publishing, 2025)
This study aims to explain the overview of patient safety optimization target three through the application of drug centralization. the research used was quantitative with a descriptive approach. The sample used was a total sampling with 16 nurses in the Cempaka room. Data was collected on patient safety target three and drug centralization through interviews, observations, and questionnairesThis study showed that most of the respondents were quite good in optimizing patient safety target three (87.5%), but in the implementation of drug centralization, the results were not good, there were 8 (50%) nurses who still did not provide the format of each type of drug when given to patients and nurses often forgot to ask for signatures after administering drugs to patients. the implementation of patient safety target three through the implementation of drug centralization is still not optimal, there are some that have not been fully implemented. Therefore. Additional motivation is needed for all nurses to consistently centralize drugs per the Standard Operating Procedures (SOP) to improve Patient Safety.